Consumer Perceptions of the U.S. Agriculture Industry Before and After Watching the Film Food, Inc. - Jessica Holt; Dwayne Cartmell (Journal of Applied Communications, 2013)
As the divide between consumers and producers in the agricultural industry increases, consumers are becoming less connected with the food they purchase. Without first-hand knowledge about the agricultural industry, consumers are relying more on the media to inform them about how their food is produced and processed. A growing form of media available to consumers is entertainment media, including documentary films. This research focuses on the ability of entertainment media to impact consumer perceptions about the agricultural industry, using the documentary film Food, Inc. The film Food, Inc. highlights aspects of the agricultural industry, including animal husbandry practices, governmental regulation of food production, and working conditions in food processing plants. This research uses a pretest and posttest to compare respondents’ perceptions about the agricultural industry before and after watching the film. Findings indicate that consumers’ perceptions were altered about the agricultural industry by watching the film. Based on this research it is recommended that future researchers and professionals in the agricultural industry work to positively influence and educate consumers about the agricultural industry through entertainment media.
Keywords: consumer perceptions; U.S. agricultural documentaries; Food; Inc.; entertainment media; and entertainment documentaries